MECHANISMS FOR IMPROVING THE STRATEGY OF ATTRACTING FOREIGN DIRECT INVESTMENT TO THE REPUBLIC OF UZBEKISTAN: EXPERIENCE OF DEVELOPED COUNTRIES (World Economics and Finance Bulletin, 2026)
Foreign direct investment (FDI) is an important method to generate sustainable economic development, technology transfer and institutional building in emerging and transitioning economies. The Republic of Uzbekistan has recently made extensive structural reforms to liberalize its economy, improve domestic and foreign investors' ability to access the investment opportunities. Notwithstanding these developments, however, when measured against developed countries the volume and quality of FDI inflows are still lower than the country’s potential. This article discusses strategies to strengthen Uzbekistan’s FDI attractiveness process through an incorporation of econometric examination and comparative policy analyses based on the experiences of developed nations. The research applied an IMRAD framework, based on annual 2010–2025 data from the Ministry of Investment, Industry and Trade of the Republic of Uzbekistan (MIIT), UNCTAD, the World Bank and OECD. Implementation of a multiple regression model and cointegration analysis have been made to explore the short- and long-run components affecting the FDI inflows. In the results, GDP growth, infrastructure improvement, exchange rate stability and quality of the institutions both significantly and positively influenced the inflow of foreign direct investment (FDI), while inflation and changes in the rate at which corporate taxes are collected also had a negative influence on it. According to MIIT data, although FDI volumes have increased significantly since 2017, investment continues to be disproportionately concentrated in extractive industries and low value addition sectors, constraining technological progress.